In search of voice and feet: A study on localization, globalization and reflexivity in Daya Pawar’s Baluta (2015) - Mwichuli, Maurice Simbili (Research Journal in Advanced Humanities, 2021)
This paper seeks to interrogate the local and global dimensions of change and reflexivity as captured in the plight and lives of the Dalit-Mahars as represented in Dagdu Daya Pawar’s Baluta. Baluta is touted as among the first autobiographical account of the ‘untouchable’ low caste Dalit-Mahars in India. First published in Marathi in 1978, it was a bold and courageous step that acted as a harbinger to other Dalit stories that opened up the virtually ‘untouchable’ world to the global scene. Although the writings have been central in the fight against the discriminative and humiliating traditions and customs in India, there is more that they actually bring to light and even more that is not said or told. Pawar himself captures this assertion in Baluta: ‘The reflection of a man in the mirror does not know the whole story of the man it is reflecting’ (Pawar, 2015:4). What is the whole story of ‘the man’ being reflected in Baluta? How does it reflect the reality locally and globally on their plight? Did the writing or movement achieve anything? These are pertinent questions that this paper seeks to address itself to.